Discapacidad visual, competencias y empleabilidad en el Perú - Bergamino Varillas, Juan Pablo (2018)
Employment is a way of economic and social development, it leads people to improve their quality of life and increase their sense of belonging, as it allows them to generate a productive contribution to society. For people with disabilities, the access to employment is usually limited because of the educational, economic and cultural barriers that prevent the participation of this group in working life; however, they have different types of skills to perform productive tasks that ensure they can maintain a stable and long term employment. It is important to know what these skills are and how they influence the employability of this group. Also, it is responsibility of the society to generate spaces for the development of this group that the government and the market have left aside.